Quality of ram semen in relation to scrotal size (Bangladesh Veterinarian, 2022)
Aim of this study was to select superior rams by assessing their scrotal size and quality of semen. In ten indigenous Bangladeshi rams, the body weight, scrotal circumference, and scrotal volume of rams increased with age (P